Enhancement of angiotensin converting enzyme (ACE) inhibitory activity of walnut peptides: Insights into the effect of ultrasound on protein structure and peptide function - Xueying Song; Ruili Liu; Yihan Mu; Shuguang Wang; Guowan Su (Food Chemistry Advances)
This study investigated the effect of ultrasound on structure of walnut protein (WP) and the release of angiotensin converting enzyme (ACE) inhibitory peptides during protein hydrolysis. The protein structure of WP was observed by fourier transform infrared (FTIR), ultraviolet–visible (UV–Vis) spectroscopy, fluorescence spectroscopy and scanning electron microscopy (SEM). Results showed that ultrasound pretreatment (UP) could induce hydrogen-bond breaking, structural unfolding and hydrophobic group exposure of WP, resulting in protein aggregates. LC−MS/MS results exhibited that the structural change of WP promoted the release of peptides containing Phe and Pro during enzymatic hydrolysis. C/N terminal-Phe and Leu-Pro were considered to be the characteristic structure of ACE inhibitory peptides released from WP by ultrasound-assisted enzymatic hydrolysis. Three novel ACE inhibitory peptides (LLPSF, LPQFF, and NLPLPF) were screened by toxicity, sensitization and molecular docking (≥-9.0 kcal/mol). Using network pharmacology to comprehensively evaluate the antihypertensive ability of the peptides, results showed that above peptides may take ACE and renin (REN) as the main targets, and exert their antihypertensive advantage through multi-target combination. GO and KEGG also highlighted their potential in regulating pathways related to hypertension and cardiovascular health.